A survey on retirements benefits of commercial companies in Malaysia / Halil Paino - Paino, Halil (Universiti Teknologi MARA Cawangan Pahang, 2003)
From the moment a person is employed, he is normally rewarded with some form of benefits. The employee benefit may take the form of immediate payment for examples salaries, bonuses, paid annual leave etc. It also may take the form of some future benefits for the employee, which might receive upon retirement. This survey was conducted as based on the information yield on the annual report or financial statement of selected commercial companies throughout Malaysia.